An online straightness deviation measurement method of rotary kiln cylinder - Kai Zheng; Yun Zhang; Lei Liu; Chen Zhao (Tehnički Vjesnik, 2017)
The straightness deviation is a key parameter to evaluate the operation state of large low-speed rotary kiln in hot state. In order to measure the straightness deviation of the kiln cylinder, a method was presented and experimentally demonstrated in real industry field in this paper. Firstly, a reference coordinate system was established on the basis of the operation principle of rotary kiln. Based on the coordinate system, the cylinder of the rotary kiln was divided into several cross sections. The geometry data of each section was collected by the designed laser system. Considering that the data contain the components of straightness deviation and kiln cylinder surface deformation, a mathematical model was proposed to process the collected data. Furthermore, a three dimensional geometry model of the kiln cylinder was set up by employing the cloud data, which can be used to provide theoretical guidance to analyse the operation state of the rotary kiln. Finally, several experiments were conducted in real industry fields to verify the proposed method, and experimental results demonstrated that the method is effective to evaluate the straightness deviation of the rotary kiln. Moreover, the measurement system is featured with small measuring error and low cost.